Implementasi Program Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) Untuk Pemberdayaan Masayarakat Miskin di Kota Padang Panjang - Mardhatillah, Muntaha (LPPM Universitas Ekasakti, 2021)
This study aims to determine how the process of implementing a business program to increase the income of a prosperous family in the city of Padang Panjang, identify the obstacles encountered and determine the efforts taken to overcome the obstacles in implementing the program. This research is motivated by not all people from the poor who are included, efforts are not carried out collectively, the lack of participation from the III plus prosperous family group to want to act as a foster father, the amount of capital provided by the government is insufficient in carrying out UPPKS activities and frequent capital. in the wrong use for consumptive purposes. The method used in the research is qualitative using descriptive methods because the research provides a description of the situation as it should be. The selection of informants was carried out by purposive sampling. The types of data are primary data and secondary data which are collected through observation, interview and documentation study. The validity test was carried out through source triangulation. Then the data analysis techniques used can be grouped into 3 stages, namely data reduction, presentation and drawing conclusions. The findings of the study indicate that the implementation of the UPPKS program is in accordance with existing procedures but has not been fully able to improve the welfare of its members and has not been optimal. This can be seen from the fact that constraints are still found in implementation, the obstacles faced in implementing the UPPKS program in the City of Padang Panjang can be categorized into two forms, namely internal constraints and external constraints. Internal constraints include weak supervision of the program, lack of capital sourced from the government, uneven coaching. And external obstacles include the use of aid funds that have not been maximized, the lack of creativity and innovation of several groups in finding and utilizing sources of funds, delays in repaying loans. To overcome obstacles in the process of implementing the UPPKS program, efforts were made, including prosperous families III as foster fathers in groups, providing guidance, and obstacles originating from program participants, such as guidance regarding the real goals of the UPPKS program, implementing a ball pick-up system. against members who are stuck in payment.